Rifampicin restores extracellular organic matrix formation and mineralization of osteoblasts after intracellular Staphylococcus aureus infection. Issue 5 (25th May 2022) - Alagboso, Francisca I.; Mannala, Gopala K.; Walter, Nike; Docheva, Denitsa; Brochhausen, Christoph; Alt, Volker; Rupp, Markus
Abstract : Aims: Bone regeneration during treatment of staphylococcal bone infection is challenging due to the ability of Staphylococcus aureus to invade and persist within osteoblasts. Here, we sought to determine whether the metabolic and extracellular organic matrix formation and mineralization ability of S. aureus -infected human osteoblasts can be restored after rifampicin (RMP) therapy. Methods: The human osteoblast-like Saos-2 cells infected with S. aureus EDCC 5055 strain and treated with 8 µg/ml RMP underwent osteogenic stimulation for up to 21 days. Test groups were Saos-2 cells + S. aureus and Saos-2 cells + S. aureus + 8 µg/ml RMP, and control groups were uninfected untreated Saos-2 cells and uninfected Saos-2 cells + 8 µg/ml RMP. Results: The S. aureus -infected osteoblasts showed a significant number of intracellular bacteria colonies and an unusual higher metabolic activity (p < 0.005) compared to uninfected osteoblasts. Treatment with 8 µg/ml RMP significantly eradicated intracellular bacteria and the metabolic activity was comparable to uninfected groups. The RMP-treated infected osteoblasts revealed a significantly reduced amount of mineralized extracellular matrix (ECM) at seven days osteogenesis relative to uninfected untreated osteoblasts (p = 0.007). Prolonged osteogenesis and RMP treatment at 21 days significantly improved the ECM mineralization level. Ultrastructural images of the mineralized RMP-treated infected osteoblasts revealed viable osteoblasts and densely distributed calcium crystal deposits within the extracellular organic matrix. The expression levels of prominent bone formation genes were comparable to the RMP-treated uninfected osteoblasts. Conclusion: Intracellular S. aureus infection impaired osteoblast metabolism and function. However, treatment with low dosage of RMP eradicated the intracellular S. aureus, enabling extracellular organic matrix formation and mineralization of osteoblasts at later stage. Cite this article: Bone Joint Res  2022;11(5):327–341.